My friend has Down syndrome - Duling, Kaitlyn (Minneapolis, MN : Bullfrog Books, 2020)
Text and illustrations show young readers how to be a good friend to people with Down syndrome.
Fun with friends -- Different strengths.
Includes index.
0.8
K-3
290L
Keywords: Down syndrome -- Juvenile literature; Children with disabilities -- Juvenile literature; Friendship -- Juvenile literature; Down syndrome; People with disabilities; Friendship; Readers (Elementary)